Differential mechanisms for TRIM32-mediated muscle tissue growth and homeostasis - Bawa, Simranjot (Kansas State University, 2020)
The decision of a cell or tissue to undergo growth or maintain homeostasis requires a delicate balance between signaling pathways. In situations that require rapid growth, metabolism may be rewired to increase cell size. One such pathway, termed glycolysis, utilizes glucose to generate energy and metabolic intermediates to produce cellular constituents, including proteins, sugars, and lipids, necessary for building biomass. This is similar to the ‘Warburg effect,’ whereby cancer cells redirect the availability of energetic substrates to generate building blocks required for the uncontrolled growth and proliferation of cells. However, mechanisms that control and promote the utilization of metabolic intermediates for the accumulation of cellular material are not fully understood. The unifying theme of this dissertation is to understand how the E3 ubiquitin ligase TRIM32 mediates the regulation and maintenance of muscle tissue in Drosophila melanogaster, where it is well-established that larval muscles alter their metabolic profile towards glycolysis to allow for a 200-fold increase in growth during development. Previous studies in our lab found that loss of Drosophila TRIM32, orthologous to the gene mutated in patients with Limb-girdle muscular dystrophy type 2H (LGMD2H), exhibit smaller muscles with progressive tissue degeneration. It was assumed that this reduced cell size was a secondary consequence of muscle deterioration. However, we made the surprising discovery that TRIM32 physically interacts with two enzymes that function in glycolysis. Furthermore, loss of TRIM32 reduces glycolytic flux, thus limiting the ability of muscle cells to produce cellular building blocks required for growth. Mutations in TRIM32 also cause a reduction in the overall size of the developing larval brain, another tissue with high glycolytic activity. This ‘Warburg-like’ elevated glycolytic rate that operates in larval muscle and brain tissue is analogous to the altered metabolism in rapidly proliferating cancer or stem cells. Since TRIM32 is upregulated in multiple types of cancer, we hypothesized that TRIM32 could be a general regulator of highly glycolytic tumor cells. Using a Drosophila wing disc tumor model, we found that Pvr-induced epithelial tumors are reduced in size upon removal of TRIM32. These findings suggest that TRIM32 directly controls cell growth, not just in muscle tissue, but in other cell types that exhibit altered metabolism to increase cell size. The pathological alleles present in LGMD2H patients vary in origin, consisting of point mutations (R394H, D487N), a single amino acid deletion (D588Δ), frameshift deletions (A422fs, T520fs, L535fs, I590fs), and a stop codon (R613*). It is not clear how these conserved mutations alter TRIM32 function. We hypothesized that similar to loss of TRIM32, LGMD2H mutations also reduce muscle size, contributing to disease pathogenesis. However, we found that transgenic expression of some of these myopathic alleles (R394H, D487N and 520fs) exhibit normal muscle growth, but rather induce myofibril abnormalities, altered nuclear morphology, and reduced TRIM32 protein levels. These results mimic phenotypes in patients afflicted with LGMD2H. We further uncovered that levels of the transmembrane proteins βPS integrin and Sarcoglycan δ (Scgδ), both core components of costameres, are elevated in Drosophila muscles expressing TRIM32 disease alleles and in mouse C2C12 muscle cells expressing an inactive version of TRIM32. These studies, taken together, have identified two independent roles of TRIM32 in the growth and maintenance of muscle tissue. TRIM32 stabilizes glycolytic enzymes to stimulate muscle growth and likely controls protein turnover of costamere components essential for myofibril stability and integrity.
Keywords: Tumor biology; LGMD2H; Muscle growth; TRIM32; Glycolytic flux